The Application of The Basic Principles of Waqf to Intellectual Property Rights (IPR) in Indonesia - Albab, Muhamad Ulil; Khanifa, Nurma Khusna; Mulyadi, Hary (Literasi Hukum, 2023)
Intellectual Property Rights (IPR) are rights owned by a person or legal entity to protect their work. The basic principles and arrangements of IPR come from the western world, among others regulated in various international treaties, while the basic principles and arrangements of waqf come from Islam. The purpose of this study is to examine and analyze the basic principles of waqf and the basic principles of Intellectual Property Rights (IPR). Conducting a comparison between the two principles which then results in the application of the basic principles of waqf to intellectual property rights. This research uses a normative juridical research method with a problem approach including a statutory approach, an analytical approach and a conceptual approach. Research specifications are focused on researching legal principles and legal synchronization. The result of this research is that the basic principles of IPR can be applied to the basic principles of waqf. The principles that can be applied include: authority rights, private and market rights, sustainability, TRIPs binding, as well as the principle of natural justice, the economic argument, the cultural argument, and the social argument.